Implementation Of Occupational Safety And Health (OSH) In Enhancing Employee Performance Contribution at CV. Serikat Maju Terus Gunungsitoli City - Selfin Murni Zalukhu; Eduar Baene; Palindungan Lahagu (Amkop Management Accounting Review (AMAR), 2026)
Occupational Safety and Health is a fundamental aspect in improving employee performance and company productivity. This research aims to analyze the implementation of Occupational Safety and Health, identify its influence on employee performance, and evaluate the constraining factors in implementing Occupational Safety and Health at CV. Serikat Maju Terus Gunungsitoli City. The research uses a qualitative approach with descriptive methods where data is obtained through in-depth interviews with informants and supported by direct observation and documentation studies. The research results show that the implementation of Occupational Safety and Health is carried out comprehensively through the provision of complete Personal Protective Equipment (PPE), periodic socialization and training, as well as compliance monitoring through routine inspections and CCTV monitoring technology. The implementation of Occupational Safety and Health has a significant positive influence on employee performance with a productivity increase of 15-20%, a decrease in workplace accident rates, reduction in lost workdays, increased job satisfaction and motivation, as well as improved work quality. The constraints faced include budget limitations, suboptimal PPE maintenance, employee awareness needs to be improved, and monitoring consistency is disrupted by operational busyness. Stronger commitment from management is needed in increasing budget allocation, strengthening PPE maintenance systems, building a safety culture, and implementing continuous education programs so that the implementation of Occupational Safety and Health is optimal and sustainable.